DEVELOPMENT OF PRIVATE PROPERTY AND BUSINESS - Borotov Alisher Khomidovich (Scholar Express Journals, 2023)
This article reveals the prospect of increasing the right to private property and entrepreneurship. The social significance of the existing legislation is analyzed. The role and importance of property rights in the development of society is based.
Keywords: Property; private property; entrepreneurship; property rights